A comparative metabolomic study of Camellia oleifera fruit under light and temperature stress. Issue 1 (31st December 2023) - Wu, Jianwen; Li, Guiqing; Guan, Jihua; Tang, Xingyue; Qiu, Mi; Yang, Suhua; Lu, Shunzhong; Fan, Xing
ABSTRACT: Camellia oleifera（C. oleifera） is one of the four main woody oils of the world. Research on improving the productivity of C. oleifera has focused on the growth process, with much less research on the mechanism of lipid accumulation post-ripening. The present study analyzed the metabolism of C. oleifera fruit under light and temperature stress and identified the primary and secondary metabolites of C. oleifera fruit using UPLC-MS. A total of 878 metabolites were detected, including 152 primary metabolites and 726 secondary metabolites, with a total of 32 core differential metabolites analyzed using a Venn diagram. After KEGG database matching, the differential metabolites were mainly enriched in the aminoacyl-tRNA synthesis pathway, the arginine and proline metabolism pathway and other pathways. Light and temperature stresses may have induced the expression of abscisic acid, arginase, and synthesized upstream substances to increase the accumulation of oils, squalene and sterols. uf0001